2021
DOI: 10.2807/1560-7917.es.2021.26.13.2100333
|View full text |Cite
|
Sign up to set email alerts
|

Linked transmission chains of imported SARS-CoV-2 variant B.1.351 across mainland France, January 2021

Abstract: Two cases of confirmed SARS-CoV-2 infection with the B.1.351 variant were reported in France in mid-January, 2020. These cases attended a gathering in Mozambique in mid-December 2020. Investigations led to the identification of five imported cases responsible for 14 transmission chains and a total 36 cases. Epidemiological characteristics seemed comparable to those described before the emergence of the South African variant B.1.351. The lack of tertiary transmission outside of the personal sphere suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“… 35 One study from France reported the incubation period of 4.50 days (95% CI, 1.83-7.17 days) for COVID-19 caused by the Beta variant. 113 Another study reported the incubation period of COVID-19 caused by the Beta/Gamma variant was 5.10 days (95% CI, 4.87-5.33 days). 35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 35 One study from France reported the incubation period of 4.50 days (95% CI, 1.83-7.17 days) for COVID-19 caused by the Beta variant. 113 Another study reported the incubation period of COVID-19 caused by the Beta/Gamma variant was 5.10 days (95% CI, 4.87-5.33 days). 35 …”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies (93 [65.5%]) were conducted between January and March 2020 and most were conducted in China (108 [76.1%]). One study used case data from multiple countries around the world, 81 6 studies were conducted in South Korea, 37 , 46 , 51 , 52 , 59 , 124 4 in France, 25 , 29 , 35 , 113 3 in Japan, 80 , 105 2 in Singapore, 87 , 111 2 in India, 16 , 78 , 83 , 103 2 in Vietnam, 21 , 58 and 2 in Australia. 45 , 99 One hundred nineteen studies (83.8%) included patients infected with the wild-type strain, 5 (3.5%) with the multiple strains, 17 , 26 , 35 , 80 , 112 and 11 (7.7%) with an unknown strain 84 , 93 , 99 , 106 , 116 , 126 , 135 , 142 , 148 , 150 , 157 (eTable 4 in the Supplement ).…”
Section: Resultsmentioning
confidence: 99%
“…In France, the incidence of COVID-19 and its mortality started rising for the third time in January 2021. This coincided with the first confirmed cases of infection with the South African VOC Beta, which arose in a group of individuals who had traveled in December 2020 to Mozambique (which shares a border with South Africa) for a religious gathering ( 10 ). This transmission event specifically changed the VOC distribution in the northeast of France.…”
Section: Introductionmentioning
confidence: 61%